Nylon composite material for blanking cap and preparation method thereof
By using nylon composite materials with modified styrene-ethylene-butene-styrene block copolymer and other components, the problems of poor heat resistance and high water absorption at high temperatures are solved, and high sealing and Good mechanical properties, suitable for automotive cover blocking applications.
Patent Information
- Application Number
- CN202310830356.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional hot melt nylon plug cover materials have poor heat resistance and high water absorption under high temperature baking conditions, resulting in seal failure and unable to meet the demand for efficient sealing in automobile production.
Nylon composite materials using 20-50% nylon, 10-50% compatibilizer, 5-30% toughener and 10-30% inorganic filler, the compatibilizer includes modified styrene-ethylene- Butene-styrene block copolymer (SEBS), nylon composite particles are prepared by premix and melt extrusion.
It realizes high heat resistance and low water absorption of nylon composite materials, while maintaining good mechanical properties, is suitable for car cover blocking, and improves sealing effect and production efficiency.
Smart Images

Figure CN119264654A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nylon composite material for a plugging cover and a preparation method thereof, in particular to a nylon composite material for a plugging cover of an automobile and a preparation method thereof. Background Art
[0002] During the production process of automobiles, manufacturing-related holes, such as sheet metal holes, are often required. For the purpose of waterproofing, corrosion prevention and noise reduction, these holes usually need to be sealed with plugs in the later stage. Currently, the commonly used plugging materials mainly include ordinary plugging materials and hot-melt plugging materials.
[0003] Common plugging materials include EPDM, TPV, TPEE and SEBS. However, these plugging materials are either generally heat-resistant or expensive, which limits their application to a certain extent.
[0004] Hot melt plugging materials are generally nylon (PA) materials, which are a type of polymer materials containing repeated amide groups in the molecular chain. Nylon materials have excellent wear resistance, scratch resistance, chemical resistance and creep resistance and are cheap, so they are widely used in automotive plugging. When in use, ethylene-vinyl acetate copolymer (EVA) hot melt adhesive rings are generally attached around the nylon plugging material, and are installed and embedded in the sheet metal hole before the car body is baked. After the EVA hot melt adhesive ring is heated and baked, the plugging cover and the sheet metal are adhered together to achieve a sealing effect.
[0005] CN115746544A discloses a super-tough nylon material for hot-melt plugging, which is prepared from the following raw materials by weight: 28-72 parts of PA resin, 0.2-0.5 parts of antioxidant, 0.2-0.5 parts of lubricant, 0.2-0.5 parts of nucleating agent, 0.2-0.5 parts of compatibilizer, 10-30 parts of rubber, 15-35 parts of elastomer, and 3-7 parts of petroleum resin. It is said that compared with the prior art, the notched impact strength of the super-tough nylon material is greatly enhanced, and the bonding strength with metal is also improved.
[0006] CN115678261A discloses a functionalized nylon composite material for automobile plugging, which is mainly prepared from the following raw materials in parts by weight: 20-40 parts of nylon; 5-20 parts of polypropylene; 10-20 parts of functionalized elastomer; 10-30 parts of toughening agent; 10-30 parts of nano inorganic powder; 3-10 parts of compatibilizer; 0.2-1 parts of heat stabilizer; 0.2-1 parts of lubricant; the functionalized elastomer is one or a mixture of two or more of styrene, olefin, urethane and ester thermoplastic elastomers. It is said that the automobile plugging nylon composite material has the advantages of mechanical impact resistance, waterproof, noise reduction, reduced vehicle weight and reduced cost.
[0007] In the process of automobile production, in order to improve the efficiency of car body baking, manufacturers often increase the baking temperature from 150℃ to 180℃ to shorten the production cycle. However, the traditional hot-melt nylon plugging material has the disadvantages of poor heat resistance and high water absorption, which causes bubbling and deformation when the baking temperature exceeds 160℃. At the same time, the nylon body with high water absorption will lose water and form water vapor during baking, which will cause a large number of pores in the EVA hot melt adhesive body, resulting in sealing failure.
[0008] Therefore, it is necessary to find a nylon composite material for plugging with high heat resistance and low water absorption without compromising its good mechanical properties. Summary of the invention
[0009] The object of the present invention is to provide a nylon composite material, comprising:
[0010] 20-50% by weight of nylon,
[0011] 10-50 wt% of a compatibilizer,
[0012] 5-30 wt% of a toughening agent, and
[0013] 10-30% by weight of inorganic filler,
[0014] The compatibilizer comprises a modified styrene-ethylene-butylene-styrene block copolymer (SEBS).
[0015] The present invention also provides a method for preparing a nylon composite material, comprising the following steps:
[0016] 1) premixing the components for forming the nylon composite material to form a premix, and
[0017] 2) The premix is melt-extruded, stretched, water-cooled and pelletized to obtain nylon composite material particles.
[0018] Beneficial effects of the present invention: The nylon composite material of the present invention has high heat resistance and low water absorption and also has good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Shows the heat resistance of nylon composites. DETAILED DESCRIPTION
[0020] Various specific embodiments, variations and examples are described herein; including exemplary embodiments and definitions adopted for understanding the claimed invention. Although the following detailed description gives specific preferred embodiments, those skilled in the art will appreciate that these embodiments are only exemplary and the invention can be practiced in other ways.
[0021] In this document, nylon and PA have the same meaning, for example, nylon 612 and PA612 have the same meaning.
[0022] In some embodiments, the nylon composite material of the present invention comprises:
[0023] 20-50% by weight of nylon,
[0024] 10-50 wt% of a compatibilizer,
[0025] 5-30 wt% of a toughening agent, and
[0026] 10-30% by weight of inorganic filler,
[0027] The compatibilizer comprises a modified styrene-ethylene-butylene-styrene block copolymer (SEBS).
[0028] In some preferred embodiments, the nylon composite material of the present invention comprises:
[0029] 30-40% by weight of nylon,
[0030] 30-40 wt% of compatibilizer,
[0031] 10-20 wt% of a toughening agent, and
[0032] 15-25% by weight of inorganic filler,
[0033] The compatibilizer comprises a modified styrene-ethylene-butylene-styrene block copolymer (SEBS).
[0034] The modified styrene-ethylene-butylene-styrene block copolymer preferably comprises maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer (MAH-g-SEBS). Preferably, the maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer has a grafting rate of 0.1-1%, such as 0.3-0.8% or 0.5-0.7%.
[0035] The maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer has a melt index of 1-30 g / 10 min measured at 210° C. and 10 kg, for example, 5-25 g / 10 min, 10-20 g / 10 min, or 12-18 g / 10 min.
[0036] In some embodiments, the nylon composite material of the present invention includes 10-50 wt % of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, preferably 10-45 wt %, more preferably 15-40 wt %, for example 20 wt %, 25 wt %, 30 wt %, 35 wt %, etc.
[0037] According to the present invention, the compatibilizer further includes other compatibilizers different from maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, such as maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), maleic anhydride grafted polypropylene (MAH-g-PP), maleic anhydride grafted ethylene propylene diene rubber (MAH-g-EPDM), maleic anhydride grafted polyethylene (MAH-g-PE), glycidyl methacrylate grafted styrene-ethylene-butylene-styrene block copolymer (GMA-g-SEBS), glycidyl methacrylate grafted ethylene-octene copolymer (GMA-g-POE), ethylene-glycidyl methacrylate-methyl acrylate copolymer (E-GMA-MA) or a combination thereof, preferably maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted polypropylene or a combination thereof.
[0038] In a preferred embodiment, the compatibilizer of the present invention comprises a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, maleic anhydride grafted polypropylene, and maleic anhydride grafted ethylene-octene copolymer.
[0039] In another preferred embodiment, the compatibilizer of the present invention comprises a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer and maleic anhydride grafted polypropylene.
[0040] In another preferred embodiment, the compatibilizer of the present invention comprises a combination of a maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer and a maleic anhydride grafted ethylene-octene copolymer.
[0041] The maleic anhydride grafted ethylene-octene copolymer preferably has a grafting rate of 0.1-0.8%, such as 0.2-0.6% or 0.3-0.5%.
[0042] The maleic anhydride grafted ethylene-octene copolymer preferably has a melt index of 1-30 g / 10 min, measured at 210° C., 10 kg, for example, 5-25 g / 10 min, 10-20 g / 10 min, or 12-18 g / 10 min.
[0043] Preferably, the nylon composite material of the present invention comprises 5-20 wt % of the maleic anhydride grafted ethylene-octene copolymer, preferably 10-15 wt %.
[0044] The maleic anhydride grafted polypropylene preferably has a grafting rate of 0.1-1%, such as 0.3-0.8% or 0.5-0.7%.
[0045] The maleic anhydride grafted polypropylene preferably has a melt index of 1-60 g / 10 min, measured at 210° C., 2.16 kg, for example, 5-50 g / 10 min, 10-40 g / 10 min, 15-35 g / 10 min or 20-30 g / 10 min.
[0046] Preferably, the nylon composite material of the present invention includes 1-10 wt % of maleic anhydride grafted polypropylene, such as 2-8 wt %, 4-6 wt %, or about 5 wt %.
[0047] According to the present invention, the nylon includes long-chain nylon or a combination of long-chain nylon and short-chain nylon. In the context of the present invention, long-chain nylon refers to nylon in which at least one monomer unit in the main chain of the nylon molecule has more than 10 carbon atoms, such as nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12. In the context of the present invention, short-chain nylon refers to nylon in which all monomer units in the main chain of the nylon molecule have less than 10 carbon atoms, such as nylon 6, nylon 46, nylon 56, nylon 66.
[0048] In some embodiments, the weight ratio of long chain nylon to short chain nylon is from 3:1 to 1:3, preferably from 2:1 to 1:2.
[0049] In some embodiments, the nylon includes nylon 6, nylon 46, nylon 56, nylon 66, nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12 or a combination thereof, preferably nylon 6, nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12 or a combination thereof, more preferably nylon 612 or a combination of nylon 612 and nylon 6.
[0050] In the present invention, there is no particular limitation on the molecular weight of nylon. Preferably, the nylon used in the present invention has a relative viscosity of 2.2-3.0.
[0051] In some embodiments, the toughening agent includes polypropylene (PP), polyethylene (PE), styrene-ethylene-butylene-styrene block copolymer (SEBS), ethylene-octene copolymer (POE), ethylene propylene diene monomer rubber (EPDM), styrene-butadiene-styrene block copolymer (SBS) or a combination thereof, preferably polypropylene (PP).
[0052] The polypropylene (PP) has a melt index of 1-80 g / 10 min, measured at 210° C., 2.16 kg, for example, 10-60 g / 10 min, 20-50 g / 10 min, or 30-40 g / 10 min.
[0053] In some embodiments, the inorganic filler used in the present invention includes calcium carbonate, glass spheres, hollow glass microspheres, glass fibers, carbon fibers, talc, wollastonite, mica flakes, calcined kaolin, barium sulfate, hydrotalcite or a combination thereof, preferably calcium carbonate.
[0054] In some embodiments, the nylon composite material of the present invention further includes 0.1-1.0 wt % of a heat stabilizer, such as 0.2 wt %, 0.3 wt %, 0.4 wt %, 0.5 wt %, 0.6 wt %, 0.7 wt %, 0.8 wt %, 0.9 wt %.
[0055] In some embodiments, the thermal stabilizer includes an antioxidant, a UV absorber, or a combination thereof.
[0056] The antioxidant includes hindered phenol, hindered amine, phosphite antioxidant or a combination thereof, such as antioxidant 1076 and antioxidant 1098.
[0057] In some embodiments, the nylon composite material of the present invention further comprises 0.1-1.0 wt % of a lubricant, such as 0.2 wt %, 0.3 wt %, 0.4 wt %, 0.5 wt %, 0.6 wt %, 0.7 wt %, 0.8 wt %, 0.9 wt %.
[0058] In some embodiments, the lubricant includes zinc stearate, calcium stearate, aluminum distearate, stearic acid, ethylene bis stearamide, or a combination thereof, preferably zinc stearate.
[0059] In one embodiment, the nylon composite material comprises:
[0060] 15-30% by weight of nylon 612,
[0061] 5-20% by weight of nylon 6,
[0062] 2-10 wt% MAH-g-PP,
[0063] 10-30 wt% MAH-g-SEBS,
[0064] 5-15 wt% MAH-g-POE,
[0065] 5-20 wt. % polypropylene, and
[0066] 10-25% by weight calcium carbonate.
[0067] In yet another embodiment, the nylon composite material comprises:
[0068] 5-20% by weight of nylon 612,
[0069] 15-30% by weight of nylon 6,
[0070] 2-10 wt% MAH-g-PP,
[0071] 10-30 wt% MAH-g-SEBS,
[0072] 5-15 wt% MAH-g-POE,
[0073] 5-20 wt. % polypropylene, and
[0074] 10-25% by weight calcium carbonate.
[0075] In yet another embodiment, the nylon composite material comprises:
[0076] 30-40% by weight of nylon 612,
[0077] 2-10 wt% MAH-g-PP,
[0078] 10-30 wt% MAH-g-SEBS,
[0079] 5-15 wt% MAH-g-POE,
[0080] 5-20 wt. % polypropylene, and
[0081] 10-25% by weight calcium carbonate.
[0082] The nylon composite material of the present invention has a Shore hardness of 45-53D, such as 48D, 49D, 50D51D or 52D.
[0083] The method for preparing the nylon composite material of the present invention comprises the following steps:
[0084] 1) premixing the components for forming the nylon composite material to form a premix, and
[0085] 2) The premix is melt-extruded, stretched, water-cooled and pelletized to obtain nylon composite material particles.
[0086] In a preferred embodiment, the components for forming the nylon composite material are premixed in a high-speed mixer to form a premix, and the premix is then melt-extruded in a twin-screw extruder preferably at 240-280° C., and stranded and water-cooled and pelletized at room temperature to obtain nylon composite material particles.
[0087] Those skilled in the art can more easily understand the present invention according to the following embodiments:
[0088] Embodiment 1. A nylon composite material comprising:
[0089] 20-50% by weight of nylon,
[0090] 10-50 wt% of a compatibilizer,
[0091] 5-30 wt% of a toughening agent, and
[0092] 10-30% by weight of inorganic filler,
[0093] The compatibilizer comprises a modified styrene-ethylene-butylene-styrene block copolymer (SEBS).
[0094] Embodiment 2. The nylon composite material according to embodiment 1, wherein the modified styrene-ethylene-butylene-styrene block copolymer comprises maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer (MAH-g-SEBS).
[0095] Embodiment 3. The nylon composite material according to Embodiment 2, wherein the maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer has a grafting rate of 0.1-1%.
[0096] Embodiment 4. The nylon composite material according to Embodiment 2, wherein the maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer has a melt index of 1-30 g / 10 min measured at 210° C., 10 kg.
[0097] Embodiment 5. The nylon composite material according to Embodiment 2, wherein the nylon composite material comprises 10-50 wt % of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, preferably 15-40 wt %.
[0098] Embodiment 6. The nylon composite material according to any of the preceding embodiments, wherein the compatibilizer further comprises maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), maleic anhydride grafted polypropylene (MAH-g-PP), maleic anhydride grafted ethylene propylene diene rubber (MAH-g-EPDM), maleic anhydride grafted polyethylene (MAH-g-PE), glycidyl methacrylate grafted styrene-ethylene-butylene-styrene block copolymer (GMA-g-SEBS), glycidyl methacrylate grafted ethylene-octene copolymer (GMA-g-POE), ethylene-glycidyl methacrylate-methyl acrylate copolymer (E-GMA-MA), or a combination thereof.
[0099] Embodiment 7. A nylon composite material according to any one of the preceding embodiments, wherein the compatibilizer comprises a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, maleic anhydride grafted polypropylene and maleic anhydride grafted ethylene-octene copolymer, or a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer and maleic anhydride grafted polypropylene, or a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer and maleic anhydride grafted ethylene-octene copolymer.
[0100] Embodiment 8 According to the nylon composite material of Embodiment 7, the maleic anhydride grafted ethylene-octene copolymer has a grafting rate of 0.1-0.8%.
[0101] Embodiment 9. The nylon composite material according to Embodiment 7, wherein the maleic anhydride grafted ethylene-octene copolymer has a melt index of 1-30 g / 10 min measured at 210° C., 10 kg.
[0102] Embodiment 10. The nylon composite material of Embodiment 7, wherein the nylon composite material comprises 5-20 wt. % of the maleic anhydride grafted ethylene-octene copolymer.
[0103] Embodiment 11. The nylon composite material according to Embodiment 7, wherein the maleic anhydride grafted polypropylene has a grafting rate of 0.1-1%.
[0104] Embodiment 12. The nylon composite material according to Embodiment 7, wherein the maleic anhydride grafted polypropylene has a melt index of 1-60 g / 10 min measured at 210° C., 2.16 kg.
[0105] Embodiment 13. The nylon composite material of Embodiment 7, wherein the nylon composite material comprises 1-10 wt. % maleic anhydride grafted polypropylene.
[0106] Embodiment 14. A nylon composite material according to any one of the preceding embodiments, wherein the nylon comprises long-chain nylon or a combination of long-chain nylon and short-chain nylon, the long-chain nylon refers to nylon in which at least one monomer unit in the main chain of the nylon molecule has more than 10 carbon atoms, and the short-chain nylon refers to nylon in which all monomer units in the main chain of the nylon molecule have less than 10 carbon atoms.
[0107] Embodiment 15. The nylon composite material according to Embodiment 14, wherein the nylon is a combination of long-chain nylon and short-chain nylon, and the short-chain nylon is nylon 6.
[0108] Embodiment 16. The nylon composite material according to Embodiment 14 or 15, wherein the weight ratio of long-chain nylon to short-chain nylon is 3:1 to 1:3, preferably 2:1 to 1:2.
[0109] Embodiment 17. A nylon composite material according to Embodiment 14, wherein the nylon comprises nylon 6, nylon 46, nylon 56, nylon 66, nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12 or a combination thereof, preferably nylon 6, nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12 or a combination thereof, more preferably nylon 612, a combination of nylon 612 and nylon 6, or a combination of nylon 1010 and nylon 6.
[0110] Embodiment 18. The nylon composite material according to any of the preceding embodiments, wherein the nylon has a relative viscosity of 2.2-3.0.
[0111] Embodiment 19. A nylon composite material according to any one of the preceding embodiments, wherein the toughening agent comprises polypropylene (PP), polyethylene (PE), styrene-ethylene-butylene-styrene block copolymer (SEBS), ethylene-octene copolymer (POE), ethylene propylene diene monomer rubber (EPDM), styrene-butadiene-styrene block copolymer (SBS) or a combination thereof, preferably polypropylene (PP).
[0112] Embodiment 20. The nylon composite material according to Embodiment 19, wherein the polypropylene (PP) has a melt index of 1-80 g / 10 min measured at 210° C., 2.16 kg.
[0113] Embodiment 21. A nylon composite material according to any one of the preceding embodiments, wherein the inorganic filler comprises calcium carbonate, glass spheres, hollow glass microspheres, glass fibers, carbon fibers, talc, wollastonite, mica flakes, calcined kaolin, barium sulfate, hydrotalcite, or a combination thereof.
[0114] Embodiment 22. The nylon composite material according to any of the preceding embodiments, wherein the nylon composite material further comprises:
[0115] 0.1-1.0 wt% heat stabilizer, and
[0116] 0.1-1.0 wt. % lubricant.
[0117] Embodiment 23. The nylon composite material of Embodiment 22, wherein the lubricant comprises zinc stearate, calcium stearate, aluminum distearate, stearic acid, ethylene bisstearamide, or a combination thereof.
[0118] Embodiment 24. The nylon composite material of Embodiment 22 or 23, wherein the thermal stabilizer comprises an antioxidant, a UV absorber, or a combination thereof.
[0119] Embodiment 25. The nylon composite material according to Embodiment 24, wherein the antioxidant comprises a hindered phenol, a hindered amine, a phosphite antioxidant, or a combination thereof.
[0120] Embodiment 26. The nylon composite material according to any of the preceding embodiments, wherein the nylon composite material has a Shore hardness of 45-53D.
[0121] Embodiment 27. The nylon composite material according to any of the preceding embodiments, wherein the nylon composite material is used in a damming cap, preferably an automotive damming cap.
[0122] Embodiment 28. A method for preparing the nylon composite material according to any one of embodiments 1-27, comprising the following steps:
[0123] 1) premixing the components for forming the nylon composite material to form a premix, and
[0124] 2) The premix is melt-extruded, stretched, water-cooled and pelletized to obtain nylon composite material particles.
[0125] The nylon composite material of the present invention is used for plugging covers, preferably automobile plugging covers. The plugging covers of the present invention can be used in any possible position of the automobile, such as the body floor, door, front fender, wheel cover and rear lower body part, and have excellent sealing performance.
[0127] The present invention is illustrated below by way of example, but it should be understood that the following examples are non-limiting and are not intended to limit the scope of protection of the present invention.
[0128] Example 1
[0129] The components corresponding to Example 1 in Table 1 were premixed in a high-speed mixer, and then the premix was melt-extruded in a twin-screw extruder at 260° C., and was stranded and water-cooled and pelletized at room temperature to obtain nylon composite material particles.
[0130] Embodiment 2-7
[0131] According to the method of Example 1, the nylon composite material particles of Examples 2-7 were prepared according to the proportions of the components in Table 1.
[0132] Table 1
[0133]
[0134] The mechanical properties of the nylon composite materials obtained in Examples 1-7 are listed in Table 2. As can be seen from Table 2, the nylon composite materials of the present invention have good mechanical properties.
[0135] Table 2
[0136]
[0137]
[0138] Comparative Examples 1-4
[0139] According to the method of Example 1, nylon composite material particles of Comparative Examples 1-4 were prepared according to the proportions of the components in Table 3.
[0140] Table 3
[0141]
[0142] The mechanical properties of the nylon composite materials obtained in Comparative Examples 1-4 are listed in Table 4. As can be seen from Table 4, the elongation at break of the nylon composite materials not containing MAH-g-SEBS in Comparative Examples 2 and 3 is poor. The Shore hardness of the nylon composite material in Comparative Example 4 reaches 55, which is too high for the application of automobile plug covers. Although the nylon composite material of Comparative Example 1 has good mechanical properties, the nylon composite material of Comparative Example 1 has a high water absorption rate, as shown in the following Table 5.
[0143] Table 4
[0144]
[0145]
[0146] Table 5 shows the saturated water absorption of the nylon composite materials of Comparative Example 1 and Examples 1-4. It can be seen from Table 5 that the water absorption of the nylon composite material of the present invention is significantly lower than that of the nylon composite material in Comparative Example 1. In addition, the nylon composite materials of Examples 5-7 also show lower water absorption than that of Comparative Example 1.
[0147] Table 5
[0148] Test items Test Method Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Saturated water absorption, 23℃ ISO 62 3.028% 1.602% 0.804% 2.326% 2.639%
[0149] Figure 1 The heat resistance of the nylon composite materials of Comparative Example 1 and Examples 1-2 is shown. Figure 1 It can be seen that the surface of the nylon composite material of the present invention is still very smooth after being heated at 180°C for 20 minutes, and there is no expansion and bubbling phenomenon, while the nylon composite material in Comparative Example 1 has expansion and bubbling phenomenon after being heated at 180°C for 20 minutes. The surface of the nylon composite material of the present invention is still very smooth even after being heated at 190°C for 20 minutes, and there is no expansion and bubbling phenomenon. It can be seen that the heat resistance of the nylon composite material of the present invention is significantly better than that of the nylon composite material in Comparative Example 1. In addition, the nylon composite materials of Examples 3-7 also show better heat resistance than Comparative Example 1, and their surfaces are still very smooth after being heated at 190°C for 20 minutes, and there is no expansion and bubbling phenomenon.
Claims
1. A nylon composite material comprising: 20-50% by weight of nylon, 10-50 wt% of a compatibilizer, 5-30 wt% of a toughening agent, and 10-30% by weight of inorganic filler, The compatibilizer comprises a modified styrene-ethylene-butylene-styrene block copolymer (SEBS).
2. The nylon composite material according to claim 1, wherein the modified styrene-ethylene-butylene-styrene block copolymer comprises maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer (MAH-g-SEBS).
3. The nylon composite material according to claim 2, wherein the maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer has a grafting rate of 0.1-1%.
4. The nylon composite material according to claim 2, wherein the maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer has a melt index of 1-30 g / 10 min measured at 210°C and 10 kg.
5. The nylon composite material according to claim 2, wherein the nylon composite material comprises 10-50 wt% of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, preferably 15-40 wt%.
6. The nylon composite material according to any of the preceding claims, wherein the compatibilizer further comprises maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), maleic anhydride grafted polypropylene (MAH-g-PP), maleic anhydride grafted ethylene propylene diene rubber (MAH-g-EPDM), maleic anhydride grafted polyethylene (MAH-g-PE), glycidyl methacrylate grafted styrene-ethylene-butylene-styrene block copolymer (GMA-g-SEBS), glycidyl methacrylate grafted ethylene-octene copolymer (GMA-g-POE), ethylene-glycidyl methacrylate-methyl acrylate copolymer (E-GMA-MA), or a combination thereof.
7. The nylon composite material according to any one of the preceding claims, wherein the compatibilizer comprises a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, maleic anhydride grafted polypropylene and maleic anhydride grafted ethylene-octene copolymer, or a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer and maleic anhydride grafted polypropylene, or a combination of maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer and maleic anhydride grafted ethylene-octene copolymer.
8. The nylon composite material according to claim 7, wherein the maleic anhydride grafted ethylene-octene copolymer has a grafting rate of 0.1-0.8%.
9. The nylon composite material according to claim 7, wherein the maleic anhydride grafted ethylene-octene copolymer has a melt index of 1-30 g / 10 min measured at 210°C, 10 kg.
10. The nylon composite material of claim 7, wherein the nylon composite material comprises 5-20 wt% of the maleic anhydride grafted ethylene-octene copolymer.
11. The nylon composite material according to claim 7, wherein the maleic anhydride grafted polypropylene has a grafting rate of 0.1-1%.
12. The nylon composite material according to claim 7, wherein the maleic anhydride grafted polypropylene has a melt index of 1-60 g / 10 min measured at 210°C, 2.16 kg.
13. The nylon composite material of claim 7, wherein the nylon composite material comprises 1-10 wt% of maleic anhydride grafted polypropylene.
14. The nylon composite material according to any one of the preceding claims, wherein the nylon comprises long-chain nylon or a combination of long-chain nylon and short-chain nylon, the long-chain nylon being nylon in which at least one monomer unit in the main chain of the nylon molecule has 10 or more carbon atoms, and the short-chain nylon being nylon in which all monomer units in the main chain of the nylon molecule have less than 10 carbon atoms. 15 . The nylon composite material according to claim 14 , wherein the nylon is a combination of long-chain nylon and short-chain nylon, and the short-chain nylon is nylon 6.
16. The nylon composite material according to claim 14 or 15, wherein the weight ratio of the long-chain nylon to the short-chain nylon is 3:1 to 1:3, preferably 2:1 to 1:
2.
17. The nylon composite material according to claim 14, wherein the nylon comprises nylon 6, nylon 46, nylon 56, nylon 66, nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12 or a combination thereof, preferably nylon 6, nylon 610, nylon 612, nylon 1010, nylon 1012, nylon 1212, nylon 11, nylon 12 or a combination thereof, more preferably nylon 612, a combination of nylon 612 and nylon 6, or a combination of nylon 1010 and nylon 6.
18. The nylon composite material of any one of the preceding claims, wherein the nylon has a relative viscosity of 2.2-3.
0.
19. The nylon composite material according to any one of the preceding claims, wherein the toughening agent comprises polypropylene (PP), polyethylene (PE), styrene-ethylene-butylene-styrene block copolymer (SEBS), ethylene-octene copolymer (POE), ethylene propylene diene monomer rubber (EPDM), styrene-butadiene-styrene block copolymer (SBS) or a combination thereof, preferably polypropylene (PP).
20. The nylon composite material according to claim 19, wherein the polypropylene (PP) has a melt index of 1-80 g / 10 min measured at 210°C, 2.16 kg.
21. The nylon composite material of any one of the preceding claims, wherein the inorganic filler comprises calcium carbonate, glass spheres, hollow glass microspheres, glass fibers, carbon fibers, talc, wollastonite, mica flakes, calcined kaolin, barium sulfate, hydrotalcite, or combinations thereof.
22. The nylon composite material of any one of the preceding claims, wherein the nylon composite material further comprises: 0.1-1.0 wt% heat stabilizer, and 0.1-1.0 wt. % lubricant.
23. The nylon composite material of claim 22, wherein the lubricant comprises zinc stearate, calcium stearate, aluminum distearate, stearic acid, ethylene bis stearamide, or a combination thereof.
24. The nylon composite material of claim 22 or 23, wherein the heat stabilizer comprises an antioxidant, an ultraviolet absorber, or a combination thereof.
25. The nylon composite material according to claim 24, wherein the antioxidant comprises a hindered phenol, a hindered amine, a phosphite antioxidant or a combination thereof.
26. The nylon composite material of any one of the preceding claims, wherein the nylon composite material has a Shore hardness of 45-53D.
27. The nylon composite material according to any one of the preceding claims, wherein the nylon composite material is used in a damming cap, preferably an automotive damming cap.
28. A method for preparing the nylon composite material according to any one of claims 1 to 27, comprising the following steps: 1) premixing the components for forming the nylon composite material to form a premix, and 2) The premix is melt-extruded, stretched, water-cooled and pelletized to obtain nylon composite material particles.